Self-esteem, peer pressure, and demographic predictors of attitude toward premarital sexual practice among first-year students of Woldia University: Implications for psychosocial intervention - Tegegne, Wossen Ayalew (Frontiers in Psychology, 2022)
Abstract Adolescence is s period of storm and stress mainly caused by dramatic social, emotional, biological, and psychological changes. Unless supported and guided by parents, teachers, peers, and other stakeholders, they may be exposed to a variety of risky sexual behaviors. In the study area, there are no research works showing the influences of peers, self-esteem, and demographic factors on premarital sexual practice among students. Ideas and knowledge gained in this area will enable the delivery of effective health and psycho social intervention strategies. Thus, the objectives of this research were to assess self-esteem, peer pressure, and demographic predictors of attitude toward premarital sex among Woldia university first-year students. Correlational design was used and 343 students were selected as samples by a simple random sampling method. Relevant information was gathered using a questionnaire. The data were quantitatively analyzed using logistic regression, one sample, and an independent sample t-test. This research work showed that level and exposure to peer pressure among first-year university students having the experience of premarital sex have below-average levels of self-esteem (t= -40.93, p=.000) and have been exposed to a higher level of peer pressure (t= 23.27, p=.000). The study suggests that male first-year students with the experience of premarital sex have a higher level of self-esteem and exposure to peer pressure than their female counterparts. Self-esteem negatively predicted attitude towards premarital sex. Therefore, the researcher recommended delivering effective counseling and gender-based guidance, and life skill training for fresh students in the university.